Substrate Impact on the Structure and Electrocatalyst Properties of Molybdenum Disulfide for HER from Water - Arūnas Jagminas; Arnas Naujokaitis; Paulius Gaigalas; Simonas Ramanavičius; Marija Kurtinaitienė; Romualdas Trusovas (Metals, 2020)
It is expected that utilization of molybdenum disulfide (MoS2)-based nanostructured electrocatalysts might replace the Pt-group electrodes most effectively applied for hydrogen evolution reaction from water. Therefore, in the past two decades, various approaches have been reported for fabrication of nanostructured MoS2-based catalysts, but their applications in practice are still missing due to lower activity and stability. We envisaged that the knowledge about the peculiarities of MoS2 nanoplatelets attachment to various conductive substrates by hydrothermal processing could be helpful for fabrication of more active and stable working electrodes. Therefore, in this study, the hydrothermal syntheses at the Mo, Ti, Al, anodized Ti, and hydrothermally designed titanium suboxide substrates were performed; the electrodes obtained were characterized; and hydrogen evolution reaction (HER) activity was tested. In this way, MoS2-based HER catalyst possessing a surprising stability and a low Tafel slope was designed via attachment of nanoplatelet-shaped MoS2 species to the nanotube-shaped anatase-TiO2 surface.